Integration and test of a degraded visual environment system on H145 - Waanders, T.; Roth, F.; Singer, B.; Fadljevic, D.; Plorin, J.; Shpak, M.; Hasharoni, O.; Limonad, A. (My University, 2019)
This paper reports on the integration, test and evaluation of a Degraded Visual Environment (DVE) system installed on an Airbus H145 (BK117 D-2) civil certified helicopter. The DVE system consists of a LiDAR sensor, an EVS camera and a head-tracked helmet mounted display system (HMD) integrated into the onboard HELIONIX® digital avionics suite. The DVE system combines sensor enhanced and synthetic elements of the external scene and provides an accurate representation of the real world for visual reference and safe manoeuvring in DVE. All systems were prototypically integrated into the H145 demonstrator in a serial-like manner, allowing for a potential serialization of the system. Extensive flight trials were conducted focusing on military as well as on civil HEMS missions and were used to verify the intended function and evaluate installed DVE system performance. The activities described herein are partially performed in the frame of a research project supported by the German Federal Office of Bundeswehr Equipment, Information Technology and In-Service Support (BAAINBw). Between November 2018 and March 2019 the system was successfully deployed in both ground and flight tests.